Internet addiction and sleep disorder in adolescents in Makassar, Indonesia - Pranoto, Amelia; Maddeppungeng, Martira; Renaldi, Rinvil; Ganda, Idham Jaya (Indonesian Pediatric Society, 2025)
Background Sleep disorders has been associated with bedtime activity, thus affected poor school performance, mood and behavioral disorders, as well as obesity. The increase of handheld media and internet use puts adolescents at higher risk of internet addiction. Increased screen time tends to increase the risk of sleep disorders. Objective To provide an overview of internet addiction in Makassar teens and its possible association with sleep disorders in adolescents. Methods This cross-sectional study was done in July to August 2021, in private junior high school, involved students aged 13-15 years. There were 196 questionnaires submitted, which was filled by the parents and the students. Data were collected online by Google form using the Kuesioner Diagnostic Adiksi Internet (KDAI) and the Sleep Disturbance Scale for Children (SDSC). Parents assisted and supervised the students while filling the questionnaire, except for the KDAI which was filled only by the student. Results There were 85 students (43.4%) identified to have internet addiction by KDAI scoring; among them, 73 students (85.90%) had sleep disorders as identified by SDSC. Internet addiction (KDAI score) and sleep disorders (SDSC) were positively and significantly associated (OR 61.4%; 95%CI 95% 25.19 TO 149.86; P<0.000). There was also a strong positive correlation in KDAI score and SDSC score (r = 0.777; P=0.000). Conclusion Internet addiction has a significant negative impact on sleep and was associated with sleep disorders in adolescents during the pandemic period.